Cultural Similarities and Differences in Relationship Goals in Intercultural Romantic Couples. (April 2021) - Fonseca, Ana Laura; Ye, Tony; Curran, Melissa; Koyama, Jill; Butler, Emily A.
Intercultural romantic relationships and multicultural families have increased in the United States and worldwide. Researchers have found that intercultural couples report high rates of conflict and relationship instability, which may be partly explained by differences between partners in relationship goals (e.g., how much intimacy is desired and how to approach conflict). Using data from 40 intercultural couples (N = 80), we test whether greater similarity in relationship goals between romantic partners is related to greater perceived partner responsiveness and, thereby, greater relationship quality. By means of Bayesian analyses, our results suggest that similarity of relationship goals is associated with both perceived responsiveness and relationship quality, but without evidence of mediation. Our results show that cultural similarities and differences exist in relationship goals in intercultural couples, and they are connected to relationship functioning. This information can be used to assist clinicians in understanding the interpersonal processes that make-up healthy relationship functioning in intercultural couples.